Flexible self-powered piezo-supercapacitor system for wearable electronics. (5th June 2018) - Gilshteyn, Evgenia P; Amanbaev, Daler; Silibin, Maxim V; Sysa, Artem; Kondrashov, Vladislav A; Anisimov, Anton S; Kallio, Tanja; Nasibulin, Albert G
Abstract: The integration of energy harvesting and energy storage in a single device both enables the conversion of ambient energy into electricity and provides a sustainable power source for various electronic devices and systems. On the other hand, mechanical flexibility, coupled with optical transparency of the energy storage devices, is required for many applications, ranging from self-powered rolled-up displays to wearable optoelectronic devices. We integrate a piezoelectric poly(vinylidene-trifluoroethylene) (P(VDF-TrFE)) film into a flexible supercapacitor system to harvest and store the energy. The asymmetric output characteristics of the piezoelectric P(VDF-TrFE) film under mechanical impacts results in effective charging of the supercapacitors. The integrated piezo-supercapacitor exhibits a specific capacitance of 50 F g −1 . The open-circuit voltage of the flexible and transparent supercapacitor reached 500 mV within 20 s during the mechanical action. Our hybridized energy harvesting and storage device can be further extended to provide a sustainable power source for various types of sensors integrated into wearable units.